Nonprofit Partisanship - Han, Baran; Ho, Benjamin; Xia, Zizhe (KDI School of Public Policy and Management, 2020)
We establish a novel measurement of nonprofit organization ideology using semantic text analysis and validate it with a large-scale online experiment. On average, health- related nonprofits as well as education-related organizations, including US universities, are the most left-leaning group. Religion-related nonprofits, on the other hand, are the most conservative. We then examine whether ”rage donations” for selected lib- eral nonprofits right after the Trump elections documented by the media hold true more generally across different sectors over different presidential elections. We find no evidence that expected shifts in ideology of a government systematically influence donations differently depending on nonprofit ideology.